3 - Idea of Emancipation and Discourse on Caste in Colonial Western India (Maharashtra) - Santosh Pandhari Suradkar (Identity, Culture and Politics, 2010)
Vibrant caste discourse took place in late 19th century Maharashtra between Nationalist, low caste movement and British Missionary, orientalist and ideologist. Therefore, this period in Maharashtra could be characterized as an age of initiation of the masses to the ideas of democracy, liberty, equality, fraternity. Caste has always been central to modern Indian politics. Even the power structure of mediaeval India was based on caste. Caste also operated as the central principle in the distribution of power and material resources in the colonial period. In India colonialism has created a democratic and modernist space; nevertheless this space was also predominantly captured by upper-caste groups. The nationalist struggle against the imperial power was aimed at establishing the caste-class hegemony. Non-Brahmin and low-caste movements were active during the colonial era, broadly pursuing two aims : achieving upward caste-class mobility and annihilation of caste. The caste system played a significant role in determining the content and direction of the processes of political socialization, political mobilization and institutionalization within the framework of modern democracy. The dynamics of caste and class were at the root of the complexity of Indian politics in its functioning. Caste and Brahminical patriarchy have consistently worked together in maintaining caste-based status and uneven distribution of material resources. As upward caste mobility also strengthens Brahminical patriarchy, the caste elites in the backward feudal states have nurtured caste mobs to protect patriarchal traditions. The new caste elites, while achieving class mobility, have maintained their social status by stringent protection of the norms of caste patriarchy. Thus the 19th century debate on caste between Nationalist, low-caste movement and British becomes significant to know present caste-class exploitation and its hegemony over the marginalized section.